Proteolytic enzymes of pond fish: methods of isolation and properties - Olga P. Dvoryaninova; Ludmila V. Antipova; Alexander V. Sokolov (Известия ТИНРО, 2016)
Methods of proteolytic enzymes isolation from muscle tissue and viscera of pond fish are viewed and their properties are investigated. Efficiency of enzymatic processes is determined by physical and chemical characteristics of the enzymes and, first of all, by their activity and stability. The cathepsins from muscle tissue of most pond fish are acidic and have the highest activity under pH 4.5-5.0. The substrate specificity of this enzyme complex predetermines its possible usage in pickling, particularly for reducing its time and improving organoleptic parameters of the product.